2004
DOI: 10.1097/00004770-200402000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Medications for Root Canal Treatment on Bonding to Root Canal Dentin

Abstract: Use of resin-based restorative materials recently has become widely accepted for treatment of endodontically treated teeth. However, some solutions routinely used during endodontic treatment procedures may have an effect on bond strengths of adhesive materials to root canal dentin. The purpose of this in vitro study was to evaluate the effect of various medications on microtensile bond strength to root canal dentin. Fourteen extracted human single-rooted teeth were used. The crowns and the pulp tissues were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
147
0
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(167 citation statements)
references
References 10 publications
9
147
0
11
Order By: Relevance
“…When shear bond test was used, other studies also showed that the application of CHX did not have a negative effect on the bond strength of adhesive systems [1,18]. On the other hand, one study even reported increased shear bond strength when CHX was used [19]. De Castro et al [18], reported that 2% CHX solution, applied before or after acid etching of the dentin, did not interfere with the µTBS of composite resin to the dentin treated with Prime&Bond NT, Single Bond or Clearfil SE Bond bonding systems.…”
Section: Discussionmentioning
confidence: 99%
“…When shear bond test was used, other studies also showed that the application of CHX did not have a negative effect on the bond strength of adhesive systems [1,18]. On the other hand, one study even reported increased shear bond strength when CHX was used [19]. De Castro et al [18], reported that 2% CHX solution, applied before or after acid etching of the dentin, did not interfere with the µTBS of composite resin to the dentin treated with Prime&Bond NT, Single Bond or Clearfil SE Bond bonding systems.…”
Section: Discussionmentioning
confidence: 99%
“…Initial free radical generation of dimethacrylate monomers is directly related to the irradiance absorbed by the composite. The rate of polymerization of the resin composites is proportional to the square root of the absorbed light intensity and photoinitiator concentration 4,18) . Besides the low light intensity as depth increases, shrinkage stress due to polymerization could lead to weakened bond strength of the cement.…”
Section: Discussionmentioning
confidence: 99%
“…50 Furthermore, it might have negative effects on the bond strength of adhesive cement to root-canal dentin. 51,52 Based on the present findings, an additional advantage of the Nd:YAG laser technique is therefore its cleaning efficacy and low tendency to produce mineral loss from the root-canal dentin. 53 …”
Section: Nd:yag and Microleakage S-47mentioning
confidence: 60%